ANALISIS HUBUNGAN LINGKUNGAN KERJA FISIK TERHADAP TERJADINYA STRES KERJA PADA PEKERJA INDUSTRI BENGKEL LAS DI KOTA PEKANBARU TAHUN 2013 (Jurnal Kajian Lingkungan, 2014)
The aim of this research to analyzed the relationship of physic environtment with worker stress on industrial worker welding shop at pekanbaru. The research method is Analytic Cross Sectional Study with total sampling method and 65 welding workshop workers as sample. Independent variable of this research is physical work environtment (noise, temperature, lighting), age, work period, time of exposure, and self safety tools. Analysis is doing by univariat, bivariate and multivariate.The result obtained is 4 variables that relationship with work stress on industrial worker welding shop that is, noise (p value: 0,004, OR: 8.119, 95% CL: 1,631-40,425), temperature (p value: 0,004, OR: 4,776, 95% CL: 1,608-14,179), lighting (p value: 0,001, OR: 7,778, 95% CL: 1,962-30,826) dan age (p value : 0,000, OR: 24,889, 95% CL: 3,019-205,154). From multivariate analysis acquired that temperature is the most dominant variable that relationship with work stress, 22 times having work stress more than worker that working at temperature < 32CKeywords: Welding, Environtment Physic, Work Stress